Structural and mechanical characteristics of magnesium-aluminate spinel crystals grown by Verneuil and Czochralski methods - Belykh, G.I.; Gritsyna, V.T.; Lytvynov, L.A.; Kol'ner, V.B. (Functional Materials, 2005)
The investigations of X-ray diffraction in magnesium aluminate spinel crystals of stoichiometric and non-stoichiometric compositions grown by Verneuil method were provided. It was revealed the decrease of MgO content at periphery to compare with that of center of crystals. The block structure of these crystals was revealed and the origin of it is discussed. There were also investigated spinel crystals grown by Czochralski method as nominally pure and doped with Mn to concentrations of 0.02, 0.04, and 0.1 mass.%. The absence of variation of composition across of radius of crystals in Czochralski grown spinel crystals was observed. More high mechanical parameters were obtained for Czochralski grown crystals. Проведено рентгенiвськi дифракцiйнi дослiдження кристалiв магнiй-алюмiнiевої Шпiнелi стехiометричного та нестехiометричного складу, вирощених методом Вернейля. 3найдено зменшення вмiсту MgO на периферiї кристалiв порiвняно з його центром. 3найдено блочну структуру цих кристалiв та обговорюються умови її створення. Дослiдженi кристали Шпiнелi, вирощенi методом Чохральського, як номiнально чистi, так i активованi iонами марганцю до концентрацiй 0,02, 0,04, та 0,1 мас%. Спостерiгалася вiдсутнiсть змiни складу вздовж радiуса кристалiв. Бiльш високi механiчнi характеристики отримано для кристалiв, вирощених методом Чохральського. Проведены рентгеновские дифрактометрические исследования кристаллов магний- алюминиевой Шпинели стехиометрического и нестехиометрического состава, выращенных методом Вернейля. Радиальное распределение состава кристаллов показывает уменьшение содержания MgO на периферии кристалла по сравнению с его центром. Обнаружена блочная структура этих кристаллов и обсуждается ее природа. Исследованы кристаллы магний-алюминиевой Шпинели, выращенные методом Чохральского, номинально чистые и легированные Mn до концентраций 0,02; 0,04 и 0,1 масс.%. Обнаружено отсутствие изменения состава вдоль радиуса кристаллов, выращенных методом Чохральского. Более высокие механические характеристики получены для кристаллов, выращенных методом Чохральского.